Association of Microvasculature and Macular Sensitivity in Idiopathic Macular Epiretinal Membrane: Using OCT Angiography and Microperimetry - Feng, Jingyang; Yang, Xiaotong; Xu, Mengqiao; Wang, Yuwei; Shi, Xiang; Zhang, Yumeng; Huang, Peirong (Frontiers in Medicine, 2021)
Purpose: To investigate the correlation between retinal capillary structure and macular function in patients with idiopathic epiretinal membrane (iERM) by using optical coherence tomography angiography (OCTA) and microperimetry. Methods: This retrospective and observational study included 30 idiopathic ERM eyes of 30 consecutive patients. OCTA was performed to evaluate macular microvasculature including the superficial capillary plexus, deep capillary plexus, and foveal avascular zone. Best corrected visual acuity (BCVA) and microperimetry were measured at baseline and 3 months after surgery. Associations between macular microvasculature and visual function were assessed. Results: Visual function including BCVA and macular sensitivity improved significantly at 3 months post-operatively (p < 0.001). At baseline, BCVA was positively correlated with foveal or parafoveal sensitivities and negatively correlated with central foveal thickness (p < 0.05). Pre-operative foveal sensitivity was significantly correlated with the vessel density of foveal or parafoveal superficial capillary plexus (p < 0.05). A multiple regression model revealed that pre-operative vessel density of foveal deep capillary plexus was an independent positive prognostic factor for post-operative BCVA (B = −0.020 ± 0.006, p = 0.006) and macular sensitivity (B = 0.200 ± 0.081, p = 0.027). Conclusion: Integrated evaluation of iERM by using OCTA and microperimetry shows an association between microvasculature and macular sensitivity. Pre-operative vessel density of foveal deep capillary plexus assessed by OCTA may be a potentially valuable prognostic factor for iERM surgery.